Juvenile cerebral ischemia reveals age-dependent BDNF–TrkB signaling changes: Novel mechanism of recovery and therapeutic intervention. Issue 12 (December 2018) - Dietz, Robert M; Orfila, James E; Rodgers, Krista M; Patsos, Olivia P; Deng, Guiying; Chalmers, Nicholas; Quillinan, Nidia; Traystman, Richard J; Herson, Paco S
Global ischemia in childhood often leads to poor neurologic outcomes, including learning and memory deficits. Using our novel model of childhood cardiac arrest/cardiopulmonary resuscitation (CA/CPR), we investigate the mechanism of ischemia-induced cognitive deficits and recovery. Memory is impaired seven days after juvenile CA/CPR and completely recovers by 30 days. Consistent with this remarkable recovery not observed in adults, hippocampal long-term potentiation (LTP) is impaired 7–14 days after CA/CPR, recovering by 30 days. This recovery is not due to the replacement of dead neurons (neurogenesis), but rather correlates with brain-derived neurotrophic factor (BDNF) expression, implicating BDNF as the molecular mechanism underlying impairment and recovery. Importantly, delayed activation of TrkB receptor signaling reverses CA/CPR-induced LTP deficits and memory impairments. These data provide two new insights (1) endogenous recovery of memory and LTP through development may contribute to improved neurological outcome in children compared to adults and (2) BDNF-enhancing drugs speed recovery from pediatric cardiac arrest during the critical school ages.